Economic Strategies and Efficiency of Power Plants in Indonesia to Achieve Net Zero Emissions - Rachmad, Rizal; Irawan, Mohammad Isa; Hanoum, Syarifa (International Journal of Energy Economics and Policy, 2024)
Indonesia is the fourth most populous country in the world. As a developing country, Indonesia needs electricity to boost its economy. Indonesia’s efforts to achieve Net Zero Emission (NZE) will have difficulty achieving this goal because fossil fuels contribute 85% of its electricity production. This study aims to measure the operational variables of CFPPs, and CO2 is used to measure efficiency to help reduce carbon gas emissions. In addition, this study attempts to analyze the factors that make CFPPs less economically profitable. Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) techniques are used to measure efficiency. The results are 23% of CFPPs are in an efficient condition. While the rest are in an inefficient condition, in the future the CFPPs can be optimized by benchmarking against their peers and increasing the target of increasingly efficient CFPPs in Indonesia. CFPPs that are close to coal mines have relatively higher operational costs but have lower CO2 emissions than CFPPs located near economic centers. Government policies are needed in efforts to encourage cheap operational costs but with low CO2 emissions as well.